Fabrication and oxidation resistance of silicon nitride fiber reinforced silica matrix wave-transparent composites. Issue 12 (December 2019) - Yang, Xuejin; Li, Bin; Li, Duan; Shao, Changwei; Zhang, Changrui; Zou, Chunrong; Liu, Kun
Abstract: Wave-transparent ceramic matrix composites for the high temperature use should possess excellent oxidation resistance. In this work, Si3 N4f /SiO2 composites with different fiber content were fabricated by filament winding and sol gel method. The oxidation resistance was investigated by tracking the response of flexural strength to the testing temperature. The results show that the flexural strength and toughness of the composites with fiber content of over 37% can reach high levels at around 175.0 MPa and 6.2 MPa m 1/2, respectively. After 1 h oxidation at 1100 °C, the flexural strength drops a lot but can still reach 114.4 MPa, which is high enough to ensure the safety of structures. However, when the oxidation temperature rises to 1200–1400 °C, the flexural strengths continue to fall to a relatively low level at 50.0–66.4 MPa. The degradation at high temperatures is caused by the combination of over strong interfacial bonding, the damage of fiber and the crystallization of silica matrix.